A taxonomic study of Senecio speciosus, Senecio macrocephalus and possible hybrid populations using morphological data, toxicty tests and chromatography - Lewis, Gillian Elizabeth (Rhodes University, Faculty of Science, Botany Department, 1995)
The variation between populations of Senecio speciosus Willd., Senecio macrocephalus DC. and intermediate plants was investigated in a comparative study of morphological characters, toxicity of plant extracts to brine shrimps (Artemia salina) and chromatography of plant extracts. Specimens were collected at 18 localities in the Eastern Cape Province. All these specimens were examined morphologically and chemical extracts were tested for toxicity and by comparative chromatography. The collection of Senecio speciosus and Senecio macrocephalus specimens in the Selmar Schonland Herbarium (GRA) was also examined morphologically. Six geographical areas were represented in the combined collections. Analysis of morphological data separated typical Senecio speciosus and Senecio macrocephalus at either end of hybrid index histograms and principal components analysis diagrams. The intermediate populations displayed morphological characters of both Senecio speciosus and Senecio macrocephalus. Some specimens were intermediate between these two species, falling within the range of variation of these species while others fell outside this range. The Brine Shrimp Assay was used to test for toxicity and to investigate the possibility of using toxicity data as a genetic marker in taxonomic studies. As Senecio speciosus extracts were less than 1% toxic and Senecio macrocephalus extracts were at least 95% toxic to the brine shrimps it is suggested that in this case toxicity can be used as a genetic marker. Toxicity can even be described as a good taxonomic character as discontinuity is very sudden and complete. The intermediate plants in the Grahamstown area were at least 92% toxic to the brine shrimps linking them to Senecio macrocephalus. Thin layer and paper chromatography were used as comparative techniques to study the chemical profiles of the specimens. Alkaloids, terpenoids and flavonoids were studied. Thin layer chromatography to separate the alkaloid components of the plant extracts showed Senecio speciosus and Senecio macrocephalus to have distinct chemical profiles suggesting that they are separate species. The intermediate plants- were found to contain chemical compounds matching either or both Senecio speciosus and Senecio macrocephalus suggesting that they may have arisen by hybridisation. In a preliminary investigation Senecio speciosus extracts showed a complete lack of terpenoid compounds whereas extracts from Senecio macrocephalus and the intermediate specimens tested gave a terpenoid colour reaction in the basal spot only. This links the intermediate populations with Senecio macrocephalus. Paper chromatography to separate the flavonoid constituents of the plant extracts also showed typical Senecio speciosus and Senecio macrocephalus to be distinct. The intermediate populations contained flavonoid compounds from one or both of these species. The populations in the Grahamstown area show morphological features close to and in some cases indistinguishable from Senecio speciosus. Chemically these specimens show some similarities with Senecio macrocephalus. In the East London area specimens show a similar mixture of characters but appear morphologically to be closer to Senecio macrocephalus. However, in the Amatole Mountains, despite both species being present in the same locality it appears that no hybridisation has occurred. It is therefore suggested that at some of the localities where the geographical ranges of Senecio speciosus and Senecio macrocephalus overlap in the Eastern Cape Province hybridisation between these two species occurs.
Keywords: Senecio; Senecio -- Analysis; Shrimps; Artemia